Seaweed Associated Macro Fauna across Seasons in the Rocky Shore Tide Pools of Sindhudurg District, Maharashtra, India - Bhave, Siddhesh; Somani, Vaishali; Quadros, Goldin (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Variation in the diversity and abundance of associated macro fauna of two commonly encountered seaweed species viz., Sargassum sp. and Amphiroa sp. were assessed seasonally. 100 grams wet weights per seaweed species in replicate were sampled from the rocky shore tide pools of Sindhudurg district of Maharashtra, India in 2021. 14 groups of macro fauna were found in association with Sargassum sp. and 18 groups with Amphiroa sp. In Sargassum sp. the highest abundance (individuals/100 grams seaweed) was recorded during Post-monsoon (116.86 ±188.24 SD), Pre-monsoon (339.65 ±347.15 SD) and Monsoon (127.14 ±67.14 SD) by Amphipoda respectively; while in Amphiroa sp. during Post-monsoon Foraminifera (740.74 ±1047.57 SD), Pre-monsoon H. Copepoda (87.80 ±3.54 SD) and Monsoon Bivalvia (55.69 ±33.19 SD). Highest biomass (mg/100 grams seaweed) in Sargassum sp. during Post-monsoon (241.51 ±429.26 SD) and Monsoon (359.76 ±356.90 SD) by Gastropoda respectively, during Pre-monsoon Amphipoda (214.55 ±191.77 SD); while in Amphiroa sp. during Post-monsoon Polychaeta (752.50 ±680.09 SD), during Pre-monsoon Gastropoda (452.68 ±457.97 SD) and during Monsoon Bivalvia (662.85 ±221.60 SD). Diversity indices in both the seaweeds during Monsoon, showed high evenness and Shannon diversity; higher dominance is seen during Pre-monsoon in Sargassum sp. and during Post-monsoon in Amphiroa sp. ANOVA and Kriskal-Wallis test showed significant variance in the abundance of Turbellaria, Ophiuroidea, Amphipoda, Isopoda, Decapoda, Tanaidacea, Copepoda, Bivalvia, Cnidaria, and Eggs. Spearman’s correlation test showed significant correlations between the environmental parameters that are pH, dissolved oxygen, conductivity, total dissolved solids, salinity, turbidity, water and air temperature and tide pool depth with the macro faunal abundance of Copepoda, Turbellaria, Ophiuroidea, Tanaidacea, Isopoda and Decapoda. Majority of macro fauna stays in association with seaweeds, as it provides food and shelter to them. Since Sargassum sp. and Amphiroa sp. were significantly available, it was selected for sampling. Study reveals both the seaweeds supports diversity of macro fauna which vary seasonally.